Special Educational Needs Prevalence in Irish-Immersion Schools - Sinéad Nic Aindriú (Encyclopedia, 2025)
For the purposes of this entry, special educational needs (SEN) refers to a condition where a student requires additional support to access education due to a disability, learning difficulty, or other developmental challenges. In this entry, an overview is provided of the prevalence of and categories of SEN in Irish-immersion primary and post-primary schools across the island of Ireland. This entry examines the prevalence and categories of SEN in Irish-immersion (IM) primary and post-primary schools across the island of Ireland. With immersion education playing a significant role in fostering bilingual proficiency, understanding SEN prevalence within these settings is critical for ensuring inclusive educational practices. The entry analyses trends over the past two decades in SEN prevalence, highlighting an increase in SEN identification, particularly in IM post-primary schools. It also explores regional disparities, comparing Gaeltacht and IM schools outside of the Gaeltacht, as well as differences between IM and English-medium education sectors. Factors such as socio-economic disadvantage, diagnostic advancements, and policy developments are considered when interpreting SEN trends. The findings contribute to the limited international research on SEN prevalence in immersion education and offer insights into recommendations in the areas of policy and practice to further support students with diverse learning needs in bilingual settings.